Increasing Representation in Clinical Images: Ludwig Angina - Ruth D. Lee; Craig R. Keenan; Arzu Ozturk; Daniel Ho; Mark C. Henderson (Annals of Internal Medicine: Clinical Cases)
We describe an African American woman with uncontrolled diabetes who presented with 3 days of jaw pain, drooling, and dysphagia due to Ludwig angina. Images include her physical examination (trismus, poor dentition, and asymmetrical tissue swelling) and radiographic findings (developing abscess). This case also illustrates why the medical education field must continue to increase representation in patients with darker skin tones in clinical images.